2 1 + 4 4 + 8 9 + 1 6 1 6 + ⋯ + 2 n n 2 + ⋯ = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Amazing Solution!
Let n = 1 ∑ ∞ 2 n n 2 = S .
Note that
S = n = 1 ∑ ∞ 2 n n 2 = n = 0 ∑ ∞ 2 n n 2
and
S = n = 1 ∑ ∞ 2 n n 2 = n = 0 ∑ ∞ 2 n + 1 ( n + 1 ) 2
Thus,
S = n = 0 ∑ ∞ 2 n n 2 = n = 0 ∑ ∞ 2 n + 1 ( n + 1 ) 2
Now let's do some rewriting:
S = 2 S − S = n = 0 ∑ ∞ 2 n ( n + 1 ) 2 − n = 0 ∑ ∞ 2 n n 2 = n = 0 ∑ ∞ 2 n 2 n + 1 = n = 0 ∑ ∞ 2 n 2 n + n = 0 ∑ ∞ 2 n 1 = 2 n = 0 ∑ ∞ 2 n 1 + n = 0 ∑ ∞ 2 n 1 = 4 + 2 = 6
There is a typo in the third line from the bottom, in the first summation it should be 2 m m
Log in to reply
Note that 2 n = 0 ∑ ∞ 2 n 1 = 2 n = 0 ∑ ∞ 2 n n .
Log in to reply
Yes, I know. I just thought it was a typo, my bad
S ⟹ 2 1 S S = n = 1 ∑ ∞ 2 n n 2 = n = 0 ∑ ∞ 2 n n 2 = n = 0 ∑ ∞ 2 ( n + 1 ) ( n + 1 ) 2 = n = 0 ∑ ∞ 2 ⋅ 2 n n 2 + 2 n + 1 = 2 1 n = 0 ∑ ∞ 2 n n 2 + 2 1 n = 1 ∑ ∞ 2 n − 1 n + 2 1 n = 0 ∑ ∞ 2 n 1 = 2 1 S + 2 1 × 4 + 2 1 ( 1 − 2 1 1 ) = 2 1 S + 2 + 1 = 3 = 6 Note that n = 1 ∑ ∞ 2 n − 1 n is sum of AGP. See note.
Note: Arithmetic-geometric progression (AGP)
k = 1 ∑ n [ a + ( k − 1 ) d ] r k − 1 = 1 − r a − [ a + ( n − 1 ) d ] r n + ( 1 − r ) 2 d r ( 1 − r n − 1 )
Problem Loading...
Note Loading...
Set Loading...
n = 0 ∑ ∞ x n = 1 − x 1 c c c c c c ∣ x ∣ < 1
Taking the derivative on both sides and multiplying by x
n = 0 ∑ ∞ n x n − 1 = ( 1 − x ) 2 1
n = 0 ∑ ∞ n x n = ( 1 − x ) 2 x
Taking the derivative and multiplying by x again
n = 0 ∑ ∞ n 2 x n − 1 = ( 1 − x ) 3 x + 1
n = 0 ∑ ∞ n 2 x n = ( 1 − x ) 3 x ( x + 1 )
We now have
S ( x ) = n = 0 ∑ ∞ n 2 x n = ( 1 − x ) 3 x ( x + 1 )
We have to find
S ( 2 1 ) = ( 1 − 2 1 ) 3 2 1 ( 2 1 + 1 ) = 6